Influence of Different Irrigation Strategies on Yield and Water Use of Dry Bean (Phaseolus vulgaris L.) in Semi-Arid Zone - NURCAN YAVUZ (Turkish Journal of Agriculture: Food Science and Technology)
Increasing population and challenges among the sectors due to the climate change and incorrect water policy has increased the pressure on water resources. This situation being as a global crisis particularly in respect to the food security has accelerated productive utilization of water supplies. The aim of the current study with 2-year experiments was to identify the effect of different irrigation interval and irrigation regimes on the yield and yield components of dry bean having greater than 50% of total world legumes production. In that experiment, two different irrigation interval, 7 and 14-day, and three different irrigation levels, (I100, I75 and I50, were studied. In results, the maximum yield was obtained from 7-day irrigation interval, and 28% yield reduction was detected at 14-day irrigation interval. In examine the irrigation levels, the highest yield was found at full irrigation (I100), and increasing water stress caused significant yield reductions e.g. 21% and 49% for I75 and I50, respectively. The evapotranspiration and total applied water as an average of 2013-2014 were calculated as 533 mm, and 450 mm, respectively. In assessment of the both the combine year results, the ky value was determined as 1.59, and this finding shows that dry bean crop is sensitive to the water stress condition.